#### Answer

$-\dfrac{8}{3}$

#### Work Step by Step

$\dfrac{y^{3}}{y^{2}-1};$ $y=-2$
Replace $y$ with $-2$ and evaluate the operations:
$\dfrac{(-2)^{3}}{(-2)^{2}-1}=\dfrac{-8}{4-1}=\dfrac{-8}{3}=-\dfrac{8}{3}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$-\dfrac{8}{3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.